2014
DOI: 10.5120/17163-7223
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Data Mining in Real Time Surface Runoff Forecasting through Support Vector Machine

Abstract: This study presents support vector machine based model for forecasting the runoff-rainfall events. A SVM based model is either implemented through Radial base or Gaussian based Kernel functions. SVM uses precipitation, temperature, sediment, rainfall, water level and discharge as input variable parameters. In this research the Sequential minimal optimization algorithm (SMO) has been implemented as an effective method for training support vector machines (SVMs) on classification tasks defined on large and spars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to their results, the predictions of the ANFIS model are more accurate than the classical models. Choubey et al (2014) used the SVM model to predict and analyze the inflow of Narmada Reservoir Dam in the Indian state of Prague showing that this method has a very good ability to simulate and predict the average monthly flow. He et al (2014) used the SVM model to predict river flow in mountainous and semi-arid regions in the northwestern part of China, and they found that SVM has better performance than ANN and ANFIS, to predict river flow in the semi-arid mountainous areas.…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, the predictions of the ANFIS model are more accurate than the classical models. Choubey et al (2014) used the SVM model to predict and analyze the inflow of Narmada Reservoir Dam in the Indian state of Prague showing that this method has a very good ability to simulate and predict the average monthly flow. He et al (2014) used the SVM model to predict river flow in mountainous and semi-arid regions in the northwestern part of China, and they found that SVM has better performance than ANN and ANFIS, to predict river flow in the semi-arid mountainous areas.…”
Section: Introductionmentioning
confidence: 99%